1985
DOI: 10.1161/01.hyp.7.5.714
|View full text |Cite
|
Sign up to set email alerts
|

Sodium balance in renal failure. A comparison of patients with normal subjects under extremes of sodium intake.

Abstract: SUMMARY To gain insight into the factors involved in the maintenance of sodium balance in patients with chronic renal failure, we studied 10 patients with a creatinine clearance of 11.5 ± 4.0 ml/min after equilibrium on 20 and 120 mEq of sodium per day. The measurements included blood pressure, plasma volume, blood volume, extracellular fluid volume, plasma renin activity, plasma aldosterone, and plasma norepinephrine. For comparison, eight normal volunteers were studied after equilibration on 20, 200, and 112… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 27 publications
3
58
0
Order By: Relevance
“…Another study has reported that the mechanism of hypertension associated with chronic kidney failure is likely to be related to the relative inability of infected kidney to excrete sodium. [32] those two studies agree with our results related to sodium level in table (2). Moreover, a recent study has indicated that 95% of filtered sodium ions were reabsorbed in chronic kidney disease.…”
Section: Introductionsupporting
confidence: 94%
“…Another study has reported that the mechanism of hypertension associated with chronic kidney failure is likely to be related to the relative inability of infected kidney to excrete sodium. [32] those two studies agree with our results related to sodium level in table (2). Moreover, a recent study has indicated that 95% of filtered sodium ions were reabsorbed in chronic kidney disease.…”
Section: Introductionsupporting
confidence: 94%
“…Likewise, sodium restriction has its greatest effect in chronic kidney disease (CKD) patients in whom sodium retention and extracellular volume expansion have a major role in hypertension [32]. Lower sodium intake markedly diminished blood pressure in patients with advanced CKD [32, 33]. It is therefore reasonable to recommend moderate salt restriction to hypertensive patients alone or in combination with antihypertensive drugs [28].…”
Section: Excess Dietary Salt and Bpmentioning
confidence: 99%
“…The volume sensitivity of blood pressure has been previously assessed with different techniques. The volume factor has been manipulated or estimated by using salt loading, 27 interdialytic weight change, 10 bioelectric impedance analysis to measure predialysis total body water 28 or postdialysis extracellular fluid volume, 29 ultrasound for determining the inferior vena cava diameter, 17 or intradialytic decrease in plasma volume calculated from predialysis and postdialysis total plasma protein concentrations. 30 In the present study, we used interdialytic weight gain to estimate the interdialytic fluid accumulation, which did not assess postdialysis volume status.…”
Section: Characteristics Of Esrd Patients With High and Low Volume Sementioning
confidence: 99%